2015
DOI: 10.1097/mph.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Standard Monitoring of Patients With Thalassemia

Abstract: Chronic transfusion therapy has played a central role in extending life expectancy for patients with hemoglobinopathies such as thalassemia. However, this life saving therapy is associated with numerous complications that now comprise the bulk of management considerations for patients with thalassemia. This review reports on the experience of the Thalassemia Longitudinal Cohort and reviews available literature to establish guidelines for the management of patients with thalassemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 65 publications
4
53
0
3
Order By: Relevance
“…Similar to other chronic diseases, thalassemia, as a chronic disease, imposes serious physical, socio-mental, congenital and economic effects to the patients and their families (8). Physical problems such as chronic anemia, bone deformation, growth change, short height and delayed physical maturing on the one hand and unpleasant as well as long and repetitive therapies on the other hand affect different life aspects of the patients (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other chronic diseases, thalassemia, as a chronic disease, imposes serious physical, socio-mental, congenital and economic effects to the patients and their families (8). Physical problems such as chronic anemia, bone deformation, growth change, short height and delayed physical maturing on the one hand and unpleasant as well as long and repetitive therapies on the other hand affect different life aspects of the patients (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the survival of TM patients has greatly improved over the last few decades as illustrated by large registries and observational cohorts (Brittenham et al, 1994;Calleja et al, 1998;Borgna-Pignatti et al, 2004a;Cunningham et al, 2004;Roudbari et al, 2008;Maggio et al, 2009a;Telfer, 2009;Marsella et al, 2010;Ladis et al, 2011;Kwiatkowski et al, 2012;Rajaeefard et al, 2015;Tubman et al, 2015;Zamani et al, 2015). Cunningham et al (2004), on behalf of the Thalassaemia Clinical Research Network (TCRN), reported such improvements and associated them with the dramatic advances in management of TM patients over the past 40 years.…”
mentioning
confidence: 99%
“…In transfusion‐dependent patients, iron overload develops after 1–2 years of regular transfusions, but hemosiderosis is also present in nontransfusion‐dependent thalassemia patients, likely because anemia and ineffective erythropoiesis cause suppression of hepcidin and increased iron absorption . Iron toxicity from hemosiderosis seems to increase reactive oxygen species (ROS) in bone marrow, worsening ineffective erythropoiesis by apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%